Superinfected and Ruptured Occipital Meningocele: Case Report - Badr Kabila MD; Meriem Zhim MD; Amine Naggar MD; Siham el Hadad PhD; Nazik Allali PhD; Latifa Chat PhD (SAGE Publishing, 2023)
Meningocele is a rare congenital malformation of the central nervous system resulting from a herniation of the meninges containing cerebrospinal fluid through a bony defect in the skull. It is part of neural tube closure anomalies. The overall incidence of meningocele is 0.8 to 3 per 10 000 live births; it varies based on geographical location and race, with a predominance of occipital localization. Among diagnostic methods, computed tomography (CT) and magnetic resonance imaging (MRI) remain crucial examinations. Prenatal diagnosis of this malformation primarily relies on ultrasound and screening through maternal serum alpha-fetoprotein (AFP) levels. They typically manifest very early at birth with a highly suggestive radioclinical presentation. Surgical treatment usually allows for a definitive cure. Superinfection and rupture of the meningocele are exceptional, resulting from delayed diagnosis and management. In several developed countries, prevention through genetic counseling and the intake of folic acid during the periconceptional period, along with accurate prenatal diagnosis and the legalization of therapeutic abortion, has led to a decrease in the prevalence of meningoceles. In less developed countries, where there is a delay in diagnosis in exceptional cases, superinfection and rupture may occur. We present the case of an 8-month-old infant with a complicated occipital meningocele with superinfection and rupture.